Imageability and legibility: cognitive analysis and visibility assessment in Galle heritage city - Abeynayake, Tharushi; Meetiyagoda, Lakshika; Kankanamge, Nayomi; Mahanama, Palpola Kankanamge Senevirathne (Journal of Architecture and Urbanism, 2022)
The concepts of imageability and legibility are important aspects of urban design. Many scholars use the terms “imageability” and “legibility” interchangeably, usually examining one concept and applying the implications to the other. This research explores the relationship between these two concepts by answering the research questions: 1. how do people perceive the saliency of landmarks (imageability) and 2. how does the spatial configuration facilitate the visibility level of landmarks (legibility)? The Galle Heritage City in Sri Lanka is considered as the case study. The first part of the empirical study is to assess the level of imageability of urban space users by completing 100 cognitive maps and producing a composite cognitive map that indicates the structural landmarks’ salience or the level of imageability. The second part is the level of legibility of the landmarks by employing the visibility assessment process and the third part compares the two results with a concurrence matrix. The findings highlight that there is a positive relationship between people’s perception (imageability) and level of visibility (legibility). Further, imageability mostly depends on semantic properties than legibility, but legibility predominantly depends on structural properties and visual properties are almost equally important to both concepts.